Thermophysical properties enhancement and characterization of CuO nanoparticles enhanced HITEC molten salt for concentrated solar power applications - Aljaerani, Hatem Ahmad; M., Samykano; A. K., Pandey; K., Kadirgama; George, Mathew; R., Saidur (Elsevier, 2022)
Molten salts are utilized in concentrated solar power (CSP) as a working fluid to store and transfer solar thermal energy. In this study, we attempted to enhance the thermal energy storage (TES) characteristics of the ternary nitrate molten salt of KNO3, NaNO2, and NaNO3, also known as HITEC molten salt, using cupric oxide (CuO) as additives for CSP applications. HITEC was doped with 0.1, 1, 3, and 5 wt% of CuO nanoparticles using the two-step wet method. Differential scanning calorimeter (DSC) was utilized to evaluate the specific heat capacity, melting point, and latent heat of the prepared material. Thermal stability was measured by thermogravimetric analysis (TGA) while the characterization analysis was performed using Fourier-Transform Infrared (FT-IR) spectroscopy, Field Emission Scanning Electron Microscope (FESEM), and Energy Dispersive X-ray Spectroscopy (EDS). The results showed that 0.1 wt% CuO nanoparticles is the optimum CuO nanoparticles concentration which resulted in a specific heat capacity enhancement of 5.6%, a 30% improvement of latent heat, and 9% enhancement of thermal stability. The morphological analysis revealed the formation of bright chain-like nanostructure due to nanoparticle dispersion, which may the possible reason for the thermophysical property enhancement.